2019
DOI: 10.3390/en12061082
|View full text |Cite
|
Sign up to set email alerts
|

Photon-Mediated Thermoelectric and Heat Currents through a Resonant Quantum Wire-Cavity System

Abstract: We theoretically consider a short quantum wire, which on both ends is connected to leads that have different temperatures. The quantum wire is assumed to be coupled to a cavity with a single-photon mode. We calculate the heat and thermoelectric currents in the quantum wire under the effect of the photon field. In the absence of the photon field, a plateau in the thermoelectric current is observed due to the thermal smearing at a high temperature gradient. In the presence of the resonance photon field, when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Asymmetric peaks in the PDOS close to the highest occupied state shown in Fig. 3, and the opening up of a bandgap are expected to increase the S, ZT and L in BLG-1, BLG-2 and BLG-3 structures [60,61]. A small bandgap of BLG-1 induces small S, ZT and L, while the largest bandgap of BLG-2 gives the maximum values of S, ZT and L. Therefore, one can expect a higher thermoelectric performance for the BLG-2.…”
Section: Thermal Propertiesmentioning
confidence: 98%
“…Asymmetric peaks in the PDOS close to the highest occupied state shown in Fig. 3, and the opening up of a bandgap are expected to increase the S, ZT and L in BLG-1, BLG-2 and BLG-3 structures [60,61]. A small bandgap of BLG-1 induces small S, ZT and L, while the largest bandgap of BLG-2 gives the maximum values of S, ZT and L. Therefore, one can expect a higher thermoelectric performance for the BLG-2.…”
Section: Thermal Propertiesmentioning
confidence: 98%
“…In previous publications, we demonstrated the effects of a photon cavity on the time-dependent electron transport in a strong electron-photon coupling regimes for both charge and thermoelectric transport through, a QD [20,21], a DQD [22], quantum wires [23][24][25] and quantum rings [26]. In theses publications, we have shown that the photon field in the cavity can be used to control the transport properties of the systems in the early transient regime were non-Markovian effects may be important.…”
Section: Introductionmentioning
confidence: 99%
“…The Si doped graphene nanosheets are called siligraphene nanosheets [42]. These two selected shapes are analogous to the triangle shape of semiconducting nanowires that have been used to control the efficiency of the solar cells [43] and the quantum dots embedded in semiconductor quantum wires used to design the resulting charge distribution [44][45][46] and thermoelectric [47] currents. Motivated by these geometrical shapes of the semiconducting materials, we consider the triangle and dot Si-dopant configurations FIG.…”
Section: Resultsmentioning
confidence: 99%